The Omani National Counterterrorism Policies and Forces (قضايا سياسية, 2022)
Collective security and international cooperation are an integral and inseparable system where the state must give and support in exchange for requesting and getting back based on reciprocity. Although parts of the approach may seem offensive, the principles and motives of the state are defensive. The data collected for this research were extracted from interviews conducted in a semi-structured style and from policy analyses achieved through observing procedures, reviewing related legislation, and a detailed review of all previously associated policies. Based on the methods used in this policy, the Sultanate of Oman has integrated collective security within its national security strategy by adopting international efforts within its guidelines. This has occurred through ratification and taking the necessary measures to implement them as part of its legislation and applying internationally agreed standards in its policies. These methods are proactive and aim to intervene and stop the terrorist attacks before they happen, eliminating the terrorist threat.